Características neonatais e maternas associadas às malformações congenitas do sistema nervoso central - Diniz, Fernanda Araújo (2016)
Congenital malformations account for 21% of deaths. The aim of this study was to analyze the neonatal and maternal changes related to malformations of the central nervous system. This is a cross-sectional, retrospective and quantitative study approach. We used secondary data collected from medical records of patients treated at a public hospital in Goiânia, GO, from 2004 to 2014. We included 87 patients in the study, who answered all the criteria adopted. Regarding the variables, the mean age was ± 24 years, and 48% declared themselves married and / or consensual union, while 26% reported being single. As for prenatal consultations, 24 (27.9%) patients had 7 or more queries, while 35 (40.7%) reported not doing any during pregnancy. 62% of children had more than 3 kg at birth and 38% were considered underweight. Most infants (43.5%) had birth weights between 2501-4000 grams. There was statistically relationship between the value of Apgar score recorded in the first minutes of life of RN's malformed. The head circumference showed a mean of 33 ± 0.2 cm. There was no significant relationship between the occurrence of CNS malformations and mortality rates in the neonatal period. The most frequent CNS malformations was hydrocephalus (in 72.1% of cases), then the myelomeningocele (13.9%). Regarding clinical characteristics and data of infants with CNS malformations, there was a predominance of males in newborns, 46 cases (55%). The most frequent CNS malformations was with hydrocephalus (72.1% of cases), then the myelomeningocele (13.9%).